2015
DOI: 10.3906/biy-1408-14
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of cordycepin on A549 human lung cancer cell line

Abstract: In the Western world, lung cancer is still a leading cause of mortality, responsible for 170,000 deaths per year, more than deaths due to breast, colon, and prostate cancer combined (Danesi et al., 2003). Approximately 80%-85% of all lung cancers are classified as nonsmallcell lung cancer (NSCLC). It is very difficult to cure NSCLC, even in the early stage, as it develops resistance against chemotherapeutic agents. Therefore, treatment of NSCLC remains elusive despite the availability of a variety of chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Several ethnopharmacological studies have demonstrated that Cordyceps extract can induce the apoptosis of human lung carcinoma cells . Tuli et al . also verified that cordycepin has the apoptotic effect on A549 human lung cancer cell line.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several ethnopharmacological studies have demonstrated that Cordyceps extract can induce the apoptosis of human lung carcinoma cells . Tuli et al . also verified that cordycepin has the apoptotic effect on A549 human lung cancer cell line.…”
Section: Discussionmentioning
confidence: 84%
“…Several ethnopharmacological studies have demonstrated that Cordyceps extract can induce the apoptosis of human lung carcinoma cells. [27,28] Tuli et al [29] also verified that cordycepin has the apoptotic effect on A549 human lung cancer cell line. In our study, flow cytometric analysis showed that the apoptosis rate of cordycepin-treated A549 and NCI-H460 cells significantly increased in a concentration-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Data about phytochemicals have proved that the synergistic properties of different flavonoids may not only be utilized to enhance the potential of chemotherapeutic drugs, but also to reduce the ineluctable side effects Tuli, Kumar, Sandhu, Sharma, & Kashyap, 2015;Tuli, Sharma, Sandhu, & Kashyap, 2013). In this scenario, KMF could act as a promising molecule to boost the therapeutic potential of the chemotherapy by refining the pharmacokinetics as well as by subsisting side effects of the therapy.…”
Section: Synergistic and Other Therapeutic Effects Of Kaempferolmentioning
confidence: 99%
“…Apoptosis, which is also called programmed cell death, is an important strategy to inhibit cancer-cell growth (Tuli et al, 2015). MLT is known to mediate both extrinsic and intrinsic pathways of apoptotic cell death (Fig.…”
Section: Induction Of Apoptosis and Cell-cycle Arrestmentioning
confidence: 99%